Rehabilitation of Nothofagus pumilio forests in Chilean Patagonia: can fencing and planting season effectively protect against exotic European hare browsing? - Herrera, Alejandro Huertas; Promis, Alvaro; Toro-Manriquez, Monica; Lencinas, Maria Vanessa; Pastur, Guillermo Martinez; Rio, Matias (My University, 2022)
In forests affected by heavy fires and continuous grazing of exotic herbivorous mammal species, Nothofagus pumilio (lenga) cannot recover naturally. The main factors that hinder the natural recovery of these forests and the feasibility of native tree plantations are the exotic herbivorous pressure, like that produced by Lepus europaeus (European hare), and the environment degradation degree by anthropic disturbances. The objective of this study was to evaluate different plantation efforts to recover N. pumilio forests degraded by fires in Chilean Patagonia. The plantation actions also included wire fences for sapling protection in 100 ha, where 60 ha were established during autumn (May 2012), and 40 ha were established during spring (October 2012). In March 2013 we recorded the height annual growth (cm year(-1)), the section browsed at each sapling, the modification of plant form (number of new branches), and the vigor expression. We evaluated the data using one- and two-way ANOVAs, Cohen's d effect size, and chi-square analyses. We measured a total of 872 plants, where 42% presented damages caused by European hare browsing. These results indicated that the wire fences were not completely useful to stop the damage on saplings (Cohen's d effect size = < 0.2). We also found that autumn plantations were more susceptible to damage than those established during spring. European hares predominantly browsed on a particular sapling section: the apical buds. As a consequence, the browsed saplings had lower height growth than undamaged ones. These outputs highlight the need to explore and implement alternative actions for the rehabilitation of these degraded deciduous forests, to achieve the objectives of sustainable management or to recover the natural ecosystem functions.
Keywords: native tree plantations; saplings; wire fences; herbivory control; lepus europaeus; aysen region